In Silico Analysis of the Antigastritis Activity of Gedi (Abelmoschus manihot) Flower Flavonoids on H2 Receptor - Adikila, Gregorius Giani; Hariyanto, Yuanita Amalia; Tallei, Trina Ekawati; Suoth, Elly Juliana; Sudewi, Sri; Fatimawali, Fatimawali (Borneo Journal of Pharmacy, 2025)
Gastritis remains a highly prevalent health concern in Indonesia, underscoring a continuous demand for innovative therapeutic interventions. The flower of Abelmoschus manihot, commonly known as Gedi, has garnered interest for its potential antigastritis properties, specifically as an H2 antagonist, attributed to its rich flavonoid content. This study aimed to rigorously evaluate the H2 antagonist potential of A. manihot flowers using an in silico approach. Our research methodology involved assessing the physicochemical and pharmacokinetic profiles, alongside molecular docking simulations, of ten prominent flavonoid ligands identified in A. manihot flowers: quercetin, myricetin, myricetin-3-O-glucoside, myricetin-3'-O-glucoside, quercetin-3'-O-glucoside, hibifolin, isoquercetin, hyperoside, quercetin-3-O-robinobioside, and rutin. The analysis of physicochemical and pharmacokinetic properties encompassed Lipinski's Rule of Five and comprehensive ADMET predictions. Molecular docking simulations focused on evaluating binding energies and interactions with crucial H2 receptor residues: Asp98, Asp186, Val99, and Phe254. Among the ligands being assessed, quercetin demonstrated the most favorable physicochemical-pharmacokinetic characteristics and exhibited superior binding affinities and interactions in the molecular docking analysis. These findings collectively suggest that A. manihot flower holds significant promise as a natural source for antigastritis agents, specifically through its potential H2 antagonist activity, with quercetin emerging as a key contributing compound.